2024
DOI: 10.1039/d3gc05157a
|View full text |Cite
|
Sign up to set email alerts
|

Cormorant-inspired macro-porous hydrogel thin film evaporators for boosting cost-effective solar water purification

Guang-Lei Ma,
Xi-Yan Qi,
Qing-Cong Wei
et al.

Abstract: Getting distilled water through solar energy is a green and sustainable way to purify water. The reduction of the evaporation enthalpy by hydrogels greatly improves the efficiency of water purification....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…52,53 Previous studies have shown that a hydrogel-based evaporator can reduce the enthalpy of water evaporation and facilitate water evaporation. 43,48 Water molecules that interact with the polymer chains could form three types of water state: bound water (BW), intermediate water (IW), and free water (FW) (Figure S8 of the Supporting Information). BW does not participate in the evaporation process because of its strong interaction with the polymer chain.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52,53 Previous studies have shown that a hydrogel-based evaporator can reduce the enthalpy of water evaporation and facilitate water evaporation. 43,48 Water molecules that interact with the polymer chains could form three types of water state: bound water (BW), intermediate water (IW), and free water (FW) (Figure S8 of the Supporting Information). BW does not participate in the evaporation process because of its strong interaction with the polymer chain.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…39 The main chain of the polymer with different hydrophilic groups could interact with water molecules, which is believed to be able to form weaker interactions and facilitate the evaporation behavior, reducing the enthalpy of evaporation and improving the efficiency of evaporation. 43 In this work, an eco-friendly 3D hydrogel-based evaporator was fabricated using the method of dipping− drying−cross-linking, which integrates carbon nanotubes (CNTs) into the sodium alginate (SA)/carboxymethyl chitosan (CMCS) hydrogel network encapsulated in a MS skeleton. SA and CMCS are natural polysaccharides derived from algae with abundant hydrophilic groups in the main chain.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation